2017
DOI: 10.1007/s12544-016-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

First aid as an important traffic safety factor – evaluation of the experience–based training

Abstract: Introduction First aid is a factor that reduces damage to health and loss of life in traffic accidents. It is therefore necessary to make even the lay population ready to give at least basic first aid. Czech driving schools offer only 4-h first-aid trainings that do not provide the appropriate level of competencies. Our team has designed a new conception of a 16-h experience-based first-aid course and compared its efficacy with the standard 4-h training. Methods Thirty participants were randomly divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
4
15
0
7
Order By: Relevance
“…The results obtained show that training program has succeeded its aims. There are some other studies which show similar findings with this study (Kureckova et al, 2017). Increase in participants' academic success is an expected outcome within context of this study.…”
Section: Discussion and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained show that training program has succeeded its aims. There are some other studies which show similar findings with this study (Kureckova et al, 2017). Increase in participants' academic success is an expected outcome within context of this study.…”
Section: Discussion and Resultssupporting
confidence: 90%
“…This kind of trainings have the potential of increasing competences of participants related to first aid. Studies which are conducted with different segments of society indicate that when educational needs of people are identified in advance who have insufficient knowledge of first aid, their first aid knowledge levels make a substantial increase at the end of training (Li et al, 2014;Kureckova et al, 2017). For this purpose, it is important to make this kind of trainings popular and increase the number of individuals who are knowledgeable about first aid for an appropriate and punctual response in first aid situations.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The results are in line with a previous review on the factors that influence the transfer of training in disaster preparedness training and also a study on barriers to implementation of CPR training, which indicated learners' preference for experience-based learning methods (22,23). The method therefore needs to focus on skill-based training for laypersons because it has been shown to be effective in imparting knowledge and skills and also in boosting participants' self-confidence as they learn to perform new skills (22). Furthermore our results pointed to the need of involving motivated trainees to train their colleagues in order to reach more participants and increase sense of ownership and sustainability of the programme.…”
Section: Discussionsupporting
confidence: 90%
“…The elderly, for example, can drive less hours per day, yet need to rest more, compared to their young colleagues. More importantly, employers in cooperation with the local government should be required to provide the periodical training [26] and alleviate the heavy burdens on employees with a reliable support system, including living allowances, on-job injury insurance, medical insurance, housing provident fund, and low-rent house, etc.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%